Элемент энергонезависимой памяти на основе квантовых точек - Слабый, К. Г.; Пащенко, А. Г. (ХНУРЕ, 2017)
This paper proposes a perspective flash memory element which is used as a storage cell array of self-assembled quantum dots as an intermediate layer in the structure of a field effect transistor with modulated doping. Described the physical basis of information storage in the proposed memory cell. A schematic structure of the element and its operation of recording, reading and erasing of information storage studied based on GaAs / AlGaAs MODFET transistor structure. Structure of a layer of quantum dots is grown on the principle of Stranski–Krastanov growth mechanism.
Keywords: Энергонезависимая память; Квантовые точки